Analysis of the Causes of Disputes in Medical Record Files for Inpatient BPJS Patients at the Imelda General Hospital for Indonesian Workers in 2022 - Geovani Arta Sihite; Rahmat Alyakin Dachi; Evawani M. Silitonga (SEAN Institute, 2023)
Coded clinical data is needed to retrieve information for the benefit of patient care, research, improving service performance, planning and resource management, and to obtain appropriate reimbursement for health services provided. The purpose of this research is to find out the causes of Dispute in Medical Record Files of BPJS Patients Hospitalization at RSU Imelda Pekerja Indonesia 2022. This type of research is qualitative with a case study approach. The method used is observation and direct interviews to the field. The subjects used in this study were the Medical Record Files of BPJS Inpatient Patients who were in dispute in October - December 2022 as many as 58 claim files. The informants used in this study were 6 BPJS Kesehatan claimants. Based on the results of the study, the causes of dispute claims on hospitalization files that were resubmitted after experiencing pending, were caused by: Administrative Disputes: Incomplete supporting requirements for submitting RITL service claims, such as action reports, procedures or operation reports, as well as supporting examinations of 2 files (4 %) from October-December 2022. Dispute Coding includes, discrepancies in the main diagnostic codes and secondary diagnoses and discrepancies in the main diagnoses and secondary diagnoses with supporting examinations on medical resumes in 28 files (48%) from October-December 2022. Medical Disputes include , medical indications are not attached (initial admission), scan results of supporting examinations are unclear and illegible, scan results of action/surgery reports are unclear and unreadable in the operation/action reports, no schedule for administration of as many drugs is attached, and discrepancies in actions or administration of drugs of the patient's main diagnoses of 28 files (48%) from October to December 2022.